2010
DOI: 10.1139/w10-034
|View full text |Cite
|
Sign up to set email alerts
|

Protection of epithelial cells from Salmonella enterica serovar Enteritidis invasion by antibodies against the SPI-1 type III secretion system

Abstract: Salmonella enterica serovar Enteritidis (Salmonella Enteritidis) is one of the major causes of bacterial food-borne illness in humans. During the course of infection, Salmonella Enteritidis uses 2 type III secretion systems (T3SS), one of which is encoded on Salmonella pathogenicity island 1 (SPI-1). SPI-1 plays a major role in the invasion process. In the present study, we evaluated the effect of sera against the SPI-1 T3SS components on invasion in vitro using polarized human intestinal epithelial cells (Cac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Proteins SseB, SipB and SipD were confirmed to be highly immunogenic during the infection. This is in agreement with previous findings [25, 26]. The level of antibodies against these proteins, measured as a density of bands on western blots, was, at least, ten times higher in a group of infected animals than in a group of control or vaccinated animals.…”
Section: Discussionsupporting
confidence: 93%
“…Proteins SseB, SipB and SipD were confirmed to be highly immunogenic during the infection. This is in agreement with previous findings [25, 26]. The level of antibodies against these proteins, measured as a density of bands on western blots, was, at least, ten times higher in a group of infected animals than in a group of control or vaccinated animals.…”
Section: Discussionsupporting
confidence: 93%
“…Some of the main variability associated with host specificity is with the secreted effectors and the SipD T3SS tip protein rather than other structural components of the respective T3SSs (206,236). The SPI-1 T3SS tip protein SipD is important for cell invasion; studies showed that antibodies directed at SipD block the ability of S. Enteritidis to invade intestinal epithelial cells (239). Effectors secreted by the SPI-I T3SS may also play a role in host specificity/range; sequence variability in the genes encoding the effector proteins SipA, SopA, and SopE and the chaperones SicP and InvB showed close evolutionary similarity in S. Enteritidis and S. Gallinarum compared to other serovars not as closely associated with avian sources (206).…”
Section: Examples Of Salmonella Host Range In Chicken-related Serovarsmentioning
confidence: 99%
“…Anti-tip protein antibodies have been shown to inhibit translocation function in T3SSs for LcrV (Pettersson et al, 1999), PcrV (Sawa et al, 1999), IpaD (Espina et al, 2006;Sani et al, 2007), and SipD (Desin et al, 2010). Antibody binding could directly interfere with tip protein function by blocking interaction with other subunits, with translocator proteins or host receptors.…”
Section: Tip Proteins As Targets Of Protective Antibodiesmentioning
confidence: 99%